Risk appetite frameworks for central banks - Škrk, Martin (knjige, 2026)
Corporate managements often implement an enterprise-wide or integrated risk appe-tite framework (RAF) as one of their business strategy tools. Industry standards, such as ISO or COSO, provide comprehensive guidance for integrating risk man-agement practices into corporate governance processes. An RAF often constitutes one of the key building blocks in business strategies. According to COSO, risk appe-tite helps an organization know when decisions are diverting efforts away from the mission and vision… Risk appetite is a fundamental part of setting strategy and ob-jectives, providing context as the organization pursues a given level of performance (Martens and Rittenberg, 2020). Banking supervision (SSM) in the EU has generally adopted a similar approach, and therefore banks and other financial institutions are encouraged to embed risk appetite in their corporate policies. The ECB considers (for credit institutions) a well-developed RAF, articulated through the risk appetite state-ment, to be a cornerstone of a sound governance framework, alongside a strong risk culture and well-defined responsibilities for risk management and control functions. It is further expected that the RAF is also being used in strategic decisions and in con-nection with the bank’s strategic processes (ECB, 2024). A similar definition of an RAF is provided by FSB (2013). In 2016, 30% of systemically important (SI) credit institutions supervised by SSM re-ported that they had developed an RAF within the last 18 months, while a further 12% had one under development (ECB, 2016). Today, the overall share of the credit institutions in the EU with a developed RAF is likely higher. This note investigates possible reasons behind such practices and proposes direc-tions for setting a holistic and strategic risk management framework with the inclusion of RAFs for central banks.
Keywords: bančni nadzor; Banke; centralne banke; elektronske knjige; Finančne institucije; kultura tveganja; Kurporativno upravljanje; Upravljanje tveganj